N-glycosylation of the transient receptor potential melastatin 8 channel is altered in pancreatic cancer cells - Roxana Ulăreanu; Gabriela Chiriţoiu; Florentina Cojocaru; Alexandru Deftu; Violeta Ristoiu; Luciana Stănică; Dan F Mihăilescu; Dana Cucu (Tumor Biology, 2017)
Transient receptor potential melastatin 8 (TRPM8), a membrane ion channel, is activated by thermal and chemical stimuli. In pancreatic ductal adenocarcinoma, TRPM8 is required for cell migration, proliferation, and senescence and is associated with tumor size and pancreatic ductal adenocarcinoma stages. Although the underlying mechanisms of these processes have yet to be described, this cation-permeable channel has been proposed as an oncological target. In this study, the glycosylation status of the TRPM8 channel was shown to affect cell proliferation, cell migration, and calcium uptake. TRPM8 expressed in the membrane of the Panc-1 pancreatic tumoral cell line is non-glycosylated, whereas human embryonic kidney cells transfected with human TRPM8 overexpress a glycosylated protein. Moreover, our data suggest that Ca 2+ uptake is modulated by the glycosylation status of the protein, thus affecting cell proliferation.